Pengaruh Gaya Kepemimpinan Demokrasi dan Koordinasi terhadap Kinerja Pegawai di Balai Penjaminan Mutu Pendidikan Provinsi Maluku - Isafa Gulo; Mohamad A. Rahawarin; Julia Th. Patty (Departement of Mathematics Education, 2023)
This research was conducted at the Maluku Province Education Quality Assurance Center against the background of the problem of employee performance that has not been maximized. Improving employee performance at the Maluku Province Education Quality Assurance Center is one of the important things. This study analyzes the effect of democratic leadership style and coordination on employee performance at the Maluku Province Education Quality Assurance Center both partially and simultaneously. This research uses descriptive quantitative research methods involving 35 respondents in filling out research questionnaires. The results showed that there was an influence of democratic leadership style and coordination on employee performance at the Maluku Province Education Quality Assurance Center both partially and simultaneously, this is seen based on the value obtained from data processing using the SPSS version 22 application which shows that the significance value (sig.) of the T test and F test is smaller than the probability value of 0.05. In improving employee performance, of course, other variables are needed to encourage better employee performance.